Lipid Transport into Bile and Role in Bile Formation - Groen, Albert K.; Elferink, Ronald P.J. Oude (Current Drug Targets - Immune, Endocrine & Metabolic Disorders, 2005)
Biliary lipid secretion is driven by bile salts, the primary metabolites of cholesterol. Transport of bile salts as well as phospholipids and cholesterol is mediated by ATP Binding Cassette (ABC) transporters. Expression of these transporters is regulated in a coordinate fashion by a set of nuclear hormone receptors explaining the old observation of coupling between bile salt secretion and biliary lipid secretion. Although it is now clear which proteins are involved, the molecular mechanism of biliary lipid secretion is still unresolved. In addition, scarce information is available about the systems responsible for intracellular transport of cholesterol, phospholipid and bile salt. These issues form the subject of the review.
Keywords: ursodeoxycholate